Effect of Hyperprolactinaemia on Male Rabbits Liver - المناف, فريال; كابان, سعاد; الشماع, وجيهة (Iraqi Journal of Science, 2025)
Eight white male NewZeland rabbits were used to study the effect of hyperprolactinaemia on the liver tissue. Suliprid (8 mg / kg) was used to elevate prolactin level in the serum four rabbits and the another four rabbits used as a control group. The liver histological study showed that there was a significant increase in the number of dinucleated parenchyma cells, significant increase in the number of Kupffer's cell and in the number of liver parenchyma diameters. Also the study showed enlargement in the central blood vessel diameter and sinusoid and increase in lymphocyte migration. The results obtained in this study showed that there was a role for prolactin on liver function.